let x1, x2 be set ; :: thesis: for C being Category
for c being Object of C
for i1, i2 being Morphism of C st x1 <> x2 holds
( c is_a_coproduct_wrt i1,i2 iff c is_a_coproduct_wrt (x1,x2) --> (i1,i2) )

let C be Category; :: thesis: for c being Object of C
for i1, i2 being Morphism of C st x1 <> x2 holds
( c is_a_coproduct_wrt i1,i2 iff c is_a_coproduct_wrt (x1,x2) --> (i1,i2) )

let c be Object of C; :: thesis: for i1, i2 being Morphism of C st x1 <> x2 holds
( c is_a_coproduct_wrt i1,i2 iff c is_a_coproduct_wrt (x1,x2) --> (i1,i2) )

let i1, i2 be Morphism of C; :: thesis: ( x1 <> x2 implies ( c is_a_coproduct_wrt i1,i2 iff c is_a_coproduct_wrt (x1,x2) --> (i1,i2) ) )
set F = (x1,x2) --> (i1,i2);
set I = {x1,x2};
assume A1: x1 <> x2 ; :: thesis: ( c is_a_coproduct_wrt i1,i2 iff c is_a_coproduct_wrt (x1,x2) --> (i1,i2) )
thus ( c is_a_coproduct_wrt i1,i2 implies c is_a_coproduct_wrt (x1,x2) --> (i1,i2) ) :: thesis: ( c is_a_coproduct_wrt (x1,x2) --> (i1,i2) implies c is_a_coproduct_wrt i1,i2 )
proof
assume A2: c is_a_coproduct_wrt i1,i2 ; :: thesis: c is_a_coproduct_wrt (x1,x2) --> (i1,i2)
then ( cod i1 = c & cod i2 = c ) ;
hence (x1,x2) --> (i1,i2) is Injections_family of c,{x1,x2} by Th65; :: according to CAT_3:def 17 :: thesis: for d being Object of C
for F9 being Injections_family of d,{x1,x2} st doms ((x1,x2) --> (i1,i2)) = doms F9 holds
ex h being Morphism of C st
( h in Hom (c,d) & ( for k being Morphism of C st k in Hom (c,d) holds
( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) iff h = k ) ) )

let b be Object of C; :: thesis: for F9 being Injections_family of b,{x1,x2} st doms ((x1,x2) --> (i1,i2)) = doms F9 holds
ex h being Morphism of C st
( h in Hom (c,b) & ( for k being Morphism of C st k in Hom (c,b) holds
( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) iff h = k ) ) )

let F9 be Injections_family of b,{x1,x2}; :: thesis: ( doms ((x1,x2) --> (i1,i2)) = doms F9 implies ex h being Morphism of C st
( h in Hom (c,b) & ( for k being Morphism of C st k in Hom (c,b) holds
( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) iff h = k ) ) ) )

assume A3: doms ((x1,x2) --> (i1,i2)) = doms F9 ; :: thesis: ex h being Morphism of C st
( h in Hom (c,b) & ( for k being Morphism of C st k in Hom (c,b) holds
( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) iff h = k ) ) )

set f = F9 /. x1;
set g = F9 /. x2;
A4: x1 in {x1,x2} by TARSKI:def 2;
then (doms ((x1,x2) --> (i1,i2))) /. x1 = dom (((x1,x2) --> (i1,i2)) /. x1) by Def1;
then dom (F9 /. x1) = dom (((x1,x2) --> (i1,i2)) /. x1) by A3, A4, Def1;
then A5: dom (F9 /. x1) = dom i1 by ;
A6: x2 in {x1,x2} by TARSKI:def 2;
then (doms ((x1,x2) --> (i1,i2))) /. x2 = dom (((x1,x2) --> (i1,i2)) /. x2) by Def1;
then dom (F9 /. x2) = dom (((x1,x2) --> (i1,i2)) /. x2) by A3, A6, Def1;
then A7: dom (F9 /. x2) = dom i2 by ;
cod (F9 /. x2) = b by ;
then A8: F9 /. x2 in Hom ((dom i2),b) by A7;
cod (F9 /. x1) = b by ;
then F9 /. x1 in Hom ((dom i1),b) by A5;
then consider h being Morphism of C such that
A9: h in Hom (c,b) and
A10: for k being Morphism of C st k in Hom (c,b) holds
( ( k (*) i1 = F9 /. x1 & k (*) i2 = F9 /. x2 ) iff h = k ) by A2, A8;
take h ; :: thesis: ( h in Hom (c,b) & ( for k being Morphism of C st k in Hom (c,b) holds
( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) iff h = k ) ) )

thus h in Hom (c,b) by A9; :: thesis: for k being Morphism of C st k in Hom (c,b) holds
( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) iff h = k )

let k be Morphism of C; :: thesis: ( k in Hom (c,b) implies ( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) iff h = k ) )

assume A11: k in Hom (c,b) ; :: thesis: ( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) iff h = k )

thus ( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) implies h = k ) :: thesis: ( h = k implies for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x )
proof
assume A12: for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ; :: thesis: h = k
then k (*) (((x1,x2) --> (i1,i2)) /. x2) = F9 /. x2 by A6;
then A13: k (*) i2 = F9 /. x2 by ;
k (*) (((x1,x2) --> (i1,i2)) /. x1) = F9 /. x1 by ;
then k (*) i1 = F9 /. x1 by ;
hence h = k by ; :: thesis: verum
end;
assume h = k ; :: thesis: for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x

then A14: ( k (*) i1 = F9 /. x1 & k (*) i2 = F9 /. x2 ) by ;
let x be set ; :: thesis: ( x in {x1,x2} implies k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x )
assume x in {x1,x2} ; :: thesis: k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x
then ( x = x1 or x = x2 ) by TARSKI:def 2;
hence k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x by A1, A14, Th3; :: thesis: verum
end;
assume A15: c is_a_coproduct_wrt (x1,x2) --> (i1,i2) ; :: thesis: c is_a_coproduct_wrt i1,i2
then A16: (x1,x2) --> (i1,i2) is Injections_family of c,{x1,x2} ;
x2 in {x1,x2} by TARSKI:def 2;
then A17: cod (((x1,x2) --> (i1,i2)) /. x2) = c by ;
x1 in {x1,x2} by TARSKI:def 2;
then cod (((x1,x2) --> (i1,i2)) /. x1) = c by ;
hence ( cod i1 = c & cod i2 = c ) by A1, A17, Th3; :: according to CAT_3:def 18 :: thesis: for d being Object of C
for f, g being Morphism of C st f in Hom ((dom i1),d) & g in Hom ((dom i2),d) holds
ex h being Morphism of C st
( h in Hom (c,d) & ( for k being Morphism of C st k in Hom (c,d) holds
( ( k (*) i1 = f & k (*) i2 = g ) iff h = k ) ) )

let d be Object of C; :: thesis: for f, g being Morphism of C st f in Hom ((dom i1),d) & g in Hom ((dom i2),d) holds
ex h being Morphism of C st
( h in Hom (c,d) & ( for k being Morphism of C st k in Hom (c,d) holds
( ( k (*) i1 = f & k (*) i2 = g ) iff h = k ) ) )

let f, g be Morphism of C; :: thesis: ( f in Hom ((dom i1),d) & g in Hom ((dom i2),d) implies ex h being Morphism of C st
( h in Hom (c,d) & ( for k being Morphism of C st k in Hom (c,d) holds
( ( k (*) i1 = f & k (*) i2 = g ) iff h = k ) ) ) )

assume that
A18: f in Hom ((dom i1),d) and
A19: g in Hom ((dom i2),d) ; :: thesis: ex h being Morphism of C st
( h in Hom (c,d) & ( for k being Morphism of C st k in Hom (c,d) holds
( ( k (*) i1 = f & k (*) i2 = g ) iff h = k ) ) )

( cod f = d & cod g = d ) by ;
then reconsider F9 = (x1,x2) --> (f,g) as Injections_family of d,{x1,x2} by Th65;
doms ((x1,x2) --> (i1,i2)) = (x1,x2) --> ((dom i1),(dom i2)) by Th6
.= (x1,x2) --> ((dom f),(dom i2)) by
.= (x1,x2) --> ((dom f),(dom g)) by
.= doms F9 by Th6 ;
then consider h being Morphism of C such that
A20: h in Hom (c,d) and
A21: for k being Morphism of C st k in Hom (c,d) holds
( ( for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x ) iff h = k ) by A15;
take h ; :: thesis: ( h in Hom (c,d) & ( for k being Morphism of C st k in Hom (c,d) holds
( ( k (*) i1 = f & k (*) i2 = g ) iff h = k ) ) )

thus h in Hom (c,d) by A20; :: thesis: for k being Morphism of C st k in Hom (c,d) holds
( ( k (*) i1 = f & k (*) i2 = g ) iff h = k )

let k be Morphism of C; :: thesis: ( k in Hom (c,d) implies ( ( k (*) i1 = f & k (*) i2 = g ) iff h = k ) )
assume A22: k in Hom (c,d) ; :: thesis: ( ( k (*) i1 = f & k (*) i2 = g ) iff h = k )
thus ( k (*) i1 = f & k (*) i2 = g implies h = k ) :: thesis: ( h = k implies ( k (*) i1 = f & k (*) i2 = g ) )
proof
assume A23: ( k (*) i1 = f & k (*) i2 = g ) ; :: thesis: h = k
now :: thesis: for x being set st x in {x1,x2} holds
k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x
let x be set ; :: thesis: ( x in {x1,x2} implies k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x )
assume x in {x1,x2} ; :: thesis: k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x
then ( x = x1 or x = x2 ) by TARSKI:def 2;
then ( ( ((x1,x2) --> (i1,i2)) /. x = i1 & F9 /. x = f ) or ( ((x1,x2) --> (i1,i2)) /. x = i2 & F9 /. x = g ) ) by ;
hence k (*) (((x1,x2) --> (i1,i2)) /. x) = F9 /. x by A23; :: thesis: verum
end;
hence h = k by ; :: thesis: verum
end;
assume A24: h = k ; :: thesis: ( k (*) i1 = f & k (*) i2 = g )
x2 in {x1,x2} by TARSKI:def 2;
then k (*) (((x1,x2) --> (i1,i2)) /. x2) = F9 /. x2 by ;
then A25: k (*) (((x1,x2) --> (i1,i2)) /. x2) = g by ;
x1 in {x1,x2} by TARSKI:def 2;
then k (*) (((x1,x2) --> (i1,i2)) /. x1) = F9 /. x1 by ;
then k (*) (((x1,x2) --> (i1,i2)) /. x1) = f by ;
hence ( k (*) i1 = f & k (*) i2 = g ) by A1, A25, Th3; :: thesis: verum